2014
DOI: 10.1186/preaccept-3516273912883547
|View full text |Cite|
|
Sign up to set email alerts
|

The RNA editing enzyme APOBEC1 induces somatic mutations and a compatible mutational signature is present in esophageal adenocarcinomas

Abstract: Background: The AID/APOBECs are deaminases that act on cytosines in a diverse set of pathways and some of them have been linked to the onset of genetic alterations in cancer. Among them, APOBEC1 is the only family member to physiologically target RNA, as the catalytic subunit in the Apolipoprotein B mRNA editing complex. APOBEC1 has been linked to cancer development in mice but its oncogenic mechanisms are not yet well understood. Results: We analyze whether expression of APOBEC1 induces a mutator phenotype in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 61 publications
6
59
0
Order By: Relevance
“…While rabbit APOBEC1 clearly has a dramatic carcinogenic effect when expressed constitutively in transgenic mice, this was not the case when expressed in rabbits [38] and it has not yet proven relevant to human cancers (although a recent study has implicated APOBEC1 in esophageal adenocarcinomas). [39] It should also be noted that this original APOBEC1 study [38] was performed prior to the discovery of AID/APOBEC catalyzed DNA cytosine deamination, [17,40] and therefore, the authors inferred that off-target RNA editing caused the observed malignancies.…”
Section: Previously Implicated Apobecsmentioning
confidence: 99%
“…While rabbit APOBEC1 clearly has a dramatic carcinogenic effect when expressed constitutively in transgenic mice, this was not the case when expressed in rabbits [38] and it has not yet proven relevant to human cancers (although a recent study has implicated APOBEC1 in esophageal adenocarcinomas). [39] It should also be noted that this original APOBEC1 study [38] was performed prior to the discovery of AID/APOBEC catalyzed DNA cytosine deamination, [17,40] and therefore, the authors inferred that off-target RNA editing caused the observed malignancies.…”
Section: Previously Implicated Apobecsmentioning
confidence: 99%
“…Overexpression of APOBEC1, APOBEC3A, and APOBEC3B is associated with increased mutation rate in vertebrate cell lines, with mutations distributed all over the genome (Saraconi et al 2014;Akre et al 2016;Green et al 2016). Notably, however, APOBEC1 causes C→A mutations in experimental systems (Saraconi et al 2014), while the heritable replication asymmetry is largely restricted to C→T and C→G mutations (Table 1). Recently, one of the alleles of APOBEC3H has been linked with lung cancer , suggesting this protein as another possible candidate.…”
Section: Apobec3a And/or Apobec3b Proteins Are Most Plausible Causes mentioning
confidence: 99%
“…While deamination in the TpCpW context excludes some APOBECs from consideration, APOBEC1, APOBEC3A, APOBEC3B, APOBEC3F, and APOBEC3H (Taylor et al 2013;Kim et al 2014;Saraconi et al 2014) all are plausible suspects. Overexpression of APOBEC1, APOBEC3A, and APOBEC3B is associated with increased mutation rate in vertebrate cell lines, with mutations distributed all over the genome (Saraconi et al 2014;Akre et al 2016;Green et al 2016). Notably, however, APOBEC1 causes C→A mutations in experimental systems (Saraconi et al 2014), while the heritable replication asymmetry is largely restricted to C→T and C→G mutations (Table 1).…”
Section: Apobec3a And/or Apobec3b Proteins Are Most Plausible Causes mentioning
confidence: 99%
“…The human and rat APOBEC1 expression vectors described in Saraconi et al 15 were digested with BglII/BsrGI to remove the IRES-EGFP sequence and ligated back after blunting the DNA ends. The APOBEC-1DC construct was obtained by PCR with primers 7 and 8 and cloned back into the pAIDexpressPuro2 backbone.…”
Section: Plasmidsmentioning
confidence: 99%
“…2,11,12 Moreover, its ability to target DNA has been linked to mutagenesis and human cancer. [13][14][15] Higher expression levels of APOBEC1 induce hyperediting of physiological RNA targets at additional sites, as well as of other genes. e.g.…”
Section: Introductionmentioning
confidence: 99%